New data on some Coccinellidae (Coleoptera) from the Mediterranean Region - Canepari, Claudio (Zootaxa, 2009)
Scymnus incisus H. Lindberg, 1931 resurrected name is a valid species, not a synonym of Nephus (Nephus) peyerimhoffi (Sicard, 1923). Nephus quadrimaculatus bucciarellii Canepari & Tedeschi, 1977 is removed from synonymy with N. (N.) ulbrichi Fürsch, 1977 and synonymized with N. (N.) schatzmayri Canepari & Tedeschi, 1977 syn. nov. Hyperaspis inexpectata Günther, 1959 resurrected name is a valid species, not a synonym of H. concolor Suffrian, 1843. Four species are newly recorded from Sardinia: Diomus rubidus (Motshulsky, 1837), Scymnus (Scymnus) femoralis (Gyllenhal, 1827), Hyperaspis (Hyperaspis) duvergeri Fürsch, 1985 and H. (H.) inexpectata Günther, 1959.